Needs Analysis Development Teaching Materials Google Sites Appreciation Fairy Tales in Elementary Schools - Alwini, Selin Nadia; Apriliya, Seni; Putri, Agnestasia Ramadhani (Jurnal Pendidikan Edutama, 2024)
Learning to appreciate fairy tales has not yet led to appreciation activities. Then, the use of teaching materials is generally still printed teaching materials. This research aims to present the results of a needs analysis for the development of Google Sites teaching materials for fairy tale appreciation learning in elementary schools. The method used in research is qualitative and data was collected through observation, interviews, document study & literature study. The research findings (1) students are more interested in digital-based learning, (2) the number of textbooks for learning activities is limited, (3) the existing teaching materials are still incomplete in explaining material regarding learning that leads to an appreciation of fairy tales. The needs analysis shows that there is a need to develop Google Sites teaching materials in learning fairy tale appreciation which can facilitate students to learn appreciation, one of them is by adding stages in appreciating fairy tales.